Sexual violence in serial form: Breaking Bad habits on TV. Issue 1 (2nd January 2019) - Joy, Stuart
Abstract: Walter White's (Bryan Cranston) attempts to isolate, degrade, exploit, frighten, and control his wife Skyler (Anna Gunn) are tactics that are well-documented in studies focusing on abuse. Yet, despite the representation of both implicit and explicit forms of domestic abuse and sexual violence throughout Breaking Bad (2008–2013), there is an apparent disconnect between how this behaviour is perceived on screen and how it is ostensibly regarded in society. It is here, at the intersection of audience reception and sociological theory that I argue Breaking Bad represents abuse as part of a broader negotiation of masculinity, one that contributes to the ongoing marginalization of women's voices in both visual media narratives and, by extension, society. In particular, I argue that despite the series' long-form structure, the lack of emphasis placed on instances of coercive control by the writers and directors is partly responsible for contributing towards a culture of misogyny and victim-blaming fostered by fans towards Skyler evident in numerous online blog posts, fan forums, social media platforms, and Anna Gunn's own treatise on the portrayal of her character in the New York Times .